PENGELOLAAN DANA DESA DALAM MENINGKATKAN PEMBANGUNAN INFRASTRUKTUR DESA KAMPUNG BARU SENTAJO KECAMATAN SENTAJO RAYA KABUPATEN KUANTAN SINGINGI TAHUN 2019-2020 - Ferren Chika Yolanda; Raja Muhammad Amin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Lack of community involvement in village fund management, especially in planning. The purpose of this study was to determine the management of village funds in Kampung Baru Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency and to determine the constraints on managing village funds in Kampung Baru Sentajo Village, Sentajo Raya District, Kuantan Singingi Regency. The research was conducted using qualitative methods. The results of this study are based on 4 principles of managing village funds, namely first, independence in the use of village funds. The Village Government of Kampung Baru Sentajo has implemented independence through the establishment of BUMDes, but the BUMDes of Kampung Baru Sentajo has not been able to provide significant assistance to Kampung Baru Sentajo's PADes. Second, priority for the use of village funds, in terms of determining priorities for the use of village funds, the Village Government does not determine based on Permendes No 16 of 2018 but from the results of the Village Conference. Third, efficiency, effectiveness and economy in the use of village funds is still lacking, this is because reports on the realization of village funds have not been opened vertically or horizontally. Fourth, the Budget Discipline that is being carried out is still using the old method by printing billboards, not yet implementing E-Government. Keywords: Principles of independence, Priority, Efficiency and Effectiveness, Economy and Budget Discipline